Problem solving and cognitive style: An error analysis - Ratnaningsih, N; Hidayat, E; Santika, S (Journal of physics. Conference series, 2020)
Problem-solving and cognitive style are two things that are important to note, but the reality is rarely considered especially cognitive style. Student cognitive style can influence problem-solving abilities. This study aims to investigate student errors based on Newman in problem solving, in terms of independent and dependent field cognitive style. The study was conducted on junior high school students in Indonesia, the method used is exploratory involving 2 Subject. Subjects are taken from independent and dependent field style cognitive groups. Stages of problem-solving according to Polya's includes: understanding the problem, devising a plan, carrying out the plan, and look back. Errors according to Newman include errors in reading, comprehension, transformation, process skills and encoding. Data were collected using the Group Embedded Figure Test (GEFT) and problem-solving test. The conclusion shows that subject with field dependent cognitive style with the initials SFD tend to make errors at the transformation stage in making models, process skills in manipulating algebra and calculation processes, and conclusions for making errors in the previous stage. Whereas subject with independent field cognitive style with the initials SFI tend to make errors at the process skill stage in manipulating algebra and calculation processes.